Plano de projeto: aplicando lições aprendidas - Leódido, Debora Castelo Branco (Universidade do Vale do Rio dos Sinos, 2014)
ABSTRACT This final project conclusion, presents a Project Plan entitled: Applying Learned Lessons. The scope of this project includes the development and deployment of a computerized software headed to apply the lessons learned on Offshore Projects. The presented plan has been prepared in total compliance with the best practices of Project Management, in accordance with the lessons of PMBOK GUIDE - 4th Edition.
Keywords: Plano de gerenciamento do projeto; Lições aprendidas; Plano do projeto; Off-Shore; Sistema informatizado; Managment plan; Learned lessons; Project Plan; Computerized Software